Community structure and genetic variation of freshwater fishes in stream and standing water in the Brantas River, Malang Regency - Restu Fitriani; Fatchur Rohman; Mohamad Amin (Jurnal Iktiologi Indonesia, 2022)
Anthropogenic activities along the Brantas River may affect the community structure and cause changes in the genetic variation of native fishes. This study aimed to analyze and compare the community structure and the genetic diversity of fishes in the standing and streamwater areas of the Brantas River. The sampling method was purposive sampling and fish samples were collected using a gill net with a horizontal transect technique. Genetic variation analysis was conducted through DNA isolation, PCR, amplification, and sequencing. A total of 14 fish species represented six families namely Chanidae, Cyprinidae, Cichlidae, Butidae, Channidae, and Mastacembelidae were recorded. Fish community structure was categorized as a moderate level of diversity with values of 1.62 and 1.88; moderate evenness with values of 0.61 and 0.75; low species richness with values of 1.86 and 1.69; and low dominance with values of 0.34 and 0.19. The Hutcheson’s T-test found significant differences in the diversity between standing water and stream water locations. The results of genetic variation analysis using the COI gene in low-abundance fish species obtained genetic differences in the Mystacoleucus marginatus sequence in standing water, shown by the substitution of three nucleotides bases at 363, 381, and 601. Meanwhile, Macrognathus aculeatus samples from this study had a 99% nucleotide similarity percentage with Macrognathus aculeatus samples in the GenBank. Abstrak Aktivitas antropogenik yang dilakukan di Sungai Brantas dapat memengaruhi struktur komunitas dan menyebabkan perubahan variasi genetik ikan asli Sungai Brantas. Penelitian ini bertujuan untuk menganalisis dan membandingkan struktur komunitas ikan, serta membedakan variasi genetik ikan di daerah mengalir dan menggenang Sungai Brantas. Metode pengambilan sampel untuk struktur komunitas secara purposive sampling menggunakan alat tangkap jaring insang dengan teknik transek horizontal. Analisis variasi genetik dengan cara isolasi DNA, PCR, amplifikasi, dan skuensing. Penelitian ini berhasil memperoleh 14 jenis ikan dari enam suku, yaitu Chanidae, Cyprinidae, Cichlidae, Butidae, Channidae, dan Mastacembelidae. Struktur komunitas di Sungai Brantas Kabupaten Malang dapat dikategorikan dengan tingkat keanekaragaman sedang dengan nilai 1,62 dan 1,88, kemerataan yang sedang dengan nilai 0,61 dan 0,75, kekayaan jenis rendah dengan nilai 1,86 dan 1,69, serta dominasi yang rendah dengan nilai 0,34 dan 0,19. Berdasarkan hasil uji t-Hutcheson diperoleh perbedaan yang signifikan pada indeks keanekaragaman antara lokasi mengalir dan menggenang. Hasil analisis variasi genetik menggunakan gen COI pada jenis ikan berkelimpahan rendah diperoleh perbedaan genetik pada sekuen Mystacoleucus marginatus di lokasi menggenang yang ditandai dengan adanya substitusi pada tiga basa nukleotida yaitu pada basa ke 363, 381, dan 601. Sampel Macrognathus aculeatus dan penelitian ini memiliki persentase kesamaan 99% dengan sampel Macrognathus aculeatus pada GenBank.